(untitled) (Ricos Biology, 2025)
Sexually Transmitted Infections (STIs) are among the most common communicable conditions worldwide, aﬀecting the health and lives of people globally. The World Health Organization estimates that over one million new STI infections occur daily among adults aged 15-49. This comprehensive review aims to provide an in-depth analysis of venereal disease transmission routes, modern diagnostic methods, available treatment options, future prognosis, emerging medications, andpreventive recommendations. This review covers major diseases such as Chlamydia, Gonorrhea, Syphilis, Human Papillomavirus (HPV), Human Immunodeﬁciency Virus (HIV), Genital Herpes, and other sexually transmitted infections.It also discusses recent advancements in molecular diagnostics, antimicrobial resistance, new preventive strategies, vaccinations, and future therapies. The ﬁndings emphasize the importance of early diagnosis, prompt treatment, and partner management in controlling the spread of these diseases. Recent data indicate that over 2.4 million cases of Syphilis, Gonorrhea, and Chlamydia were diagnosed and reported in the United States in 2023, underscoring the continuous need for comprehensive prevention and treatment strategies.